Hoisting sails toward Itaca. Statute of the San Carlos de Lima’s Convictorio - Huaraj Acuña, Juan Carlos (2009)
The Convictorio of San Carlos from Lima, was an institution founded for the viceregal State in 1769 in substitution of the noted Jesuit noted school that closed after its expulsion in 1767. The time bigger celebrity and duration corresponded to the rectorado of Toribio Rodríguez of Mendoza who directed its cloisters during almost 30 years, until it presented its renouncement before the viceroy Joaquín of Pezuela, due mainly to the economic anguishing situation that happened to this educational institution before the Emancipation. The present article is focused in the «Statute for Convictorio» proposed by Jerónimo of Agüero, document that governed from 1829 to 1839. In this year it coincides with the arrival to the government of this House of Studies of Bartolomé Herrera who observed an ideological concrete address, giving new airs to the political conservative positions, group of influential ideas until ends of the century nineteen inclusive. The text is part of the history previous to its arrival.